Il lavoro di équipe nella sezione “Minorati psichici” - Loppi, Francesca; Giordano, Francesca; Padrevecchi, Francesca (Il sogno della farfalla, 2022)
This article gathers three reports which analyze a clinical experience with patients convicted for crimes in Rome’s Rebibbia special wing. This therapeutic process has relied on the work of a multidisciplinary health care worker team. The treatment, which included psychiatric, psychological, and rehabilitative intervention was exclusively provided to sixteen patients affected by mental illness. The therapeutic tools adopted included the importance of the “presence”, as a therapeutic factors, the attempt to interpret the conscious and non-conscious relational dynamics and finally rehabilitative activities. After a long and complex work, a first result was achieved: the single individuals gathered in a community of patients similarly to those organized in therapeutic communities. Finally, the authors describe the attempt to maintain this group image despite the preventive distancing measure adopted to avoid Covid 19 infection.